2014
DOI: 10.1056/nejmoa1304127
|View full text |Cite
|
Sign up to set email alerts
|

Global Sodium Consumption and Death from Cardiovascular Causes

Abstract: In this modeling study, 1.65 million deaths from cardiovascular causes that occurred in 2010 were attributed to sodium consumption above a reference level of 2.0 g per day. (Funded by the Bill and Melinda Gates Foundation.).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

18
767
4
28

Year Published

2016
2016
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 1,024 publications
(817 citation statements)
references
References 35 publications
18
767
4
28
Order By: Relevance
“…Excess sodium intake can increase blood pressure and risk for cardiovascular disease (2,3). To determine the availability and promotion of lower-sodium options in the nutrition environment, the Guam Department of Public Health and Social Services (DPHSS) conducted an assessment in September 2015 using previously validated tools adapted to include sodium measures.…”
mentioning
confidence: 99%
“…Excess sodium intake can increase blood pressure and risk for cardiovascular disease (2,3). To determine the availability and promotion of lower-sodium options in the nutrition environment, the Guam Department of Public Health and Social Services (DPHSS) conducted an assessment in September 2015 using previously validated tools adapted to include sodium measures.…”
mentioning
confidence: 99%
“…The mean global salt intake in 2010 was estimated to be around 10 g per person a day, corresponding to 4 g/day of sodium, which is twice the reference level recommended by the World Health Organization 73. The salt consumption varies considerably among countries, ranging from 1.5 g of sodium per day in East African countries to 3.9 g of sodium per day in high‐income countries 73.…”
Section: Salt and Msmentioning
confidence: 99%
“…The salt consumption varies considerably among countries, ranging from 1.5 g of sodium per day in East African countries to 3.9 g of sodium per day in high‐income countries 73. Recently, many studies have demonstrated that a high intake of sodium chloride can be an important factor potentially influencing autoimmunity in both humans and rodents 74, 75, 76, 77, 78, 79, 80, 81, 82.…”
Section: Salt and Msmentioning
confidence: 99%
“…Entre los factores de riesgo modificables están el consumo de tabaco, actividad física insuficiente, uso nocivo de alcohol e ingesta excesiva de sal/sodio. Entre los factores cardio-metabólicos se tiene la hipertensión, hiperglucemia, dislipidemia, sobrepeso y obesidad (5,6) . Por eso, es necesario comprender que gran parte de los problemas de salud del adulto se originan en edades tempranas, incluso desde la vida intrauterina, haciendo posibles la prevención, detección y tratamiento precoces.…”
Section: Introductionunclassified